Enhancement of hydrogen and methane production from co-digestion of food waste and chicken manure - Mat Saad, Mohd Faiz (2017)
The demand for clean energy from renewable resources stimulates biohydrogen and biomethane production from agro-food waste as an alternative fuel to replace fossil fuel. A combined production of biohydrogen and biomethane has attracted growing attention of researchers and industries worldwide due to their potential as fuel substitute. Biosynthesis of biohydrogen and biomethane from food waste and chicken manure fermentation initiates clean technologies for energy generation thus provide the solution for waste treatment. Despite that, biogas production of hydrogen and methane have limiting factors that relate to soluble metabolites and active microorganisms. This inhibition effects can be overcome by optimizing several factors for biohydrogen and biomethane production. The objectives of this study were to determine the best ratio of food waste and chicken manure for biogas production in batch fermentation and to evaluate the effect of different inoculums and heat treatment upon selected inoculum on biohydrogen and biomethane production besides the microbial diversity in the fermentation using Next Generation Sequencing (NGS) of 16S ribosomal RNA were also carried out. The batch fermentation was conducted using 150 mL serum bottles incubated in anaerobic condition. Food waste with composition ratios of 3:1:1 of carbohydrates, protein and fiber were used as substrate added with chicken manure freshly collected from poultry farm. Biohydrogen and biomethane production were tested for the effects of different substrate ratio, different inoculums and heat treatment on selected inoculums. Temperature and initial pH were kept constant at 35°C and initial pH 7. Biohydrogen and biomethane from food waste and chicken manure was performed at different ratio (40:60, 50:50, 60:40 and 70:30 (v/v)) inoculated with aeration tank sludge (ATS), return activated sludge (RAS) and palm oil mill effluent (POME) sludge. Heat treatment was carried out at 80°C for 20 minutes to eliminate the nonsporing bacteria. Biogas was collected daily throughout 10 days fermentation and the composition of hydrogen and methane in the biogas was analyzed by gas chromatography. The highest biogas yield obtained was 111.72 NmL/g TSS for the experiment conducted at 50:50 (v/v) substrate ratio added with RAS as inoculum without heat treatment. The highest percentages of hydrogen and methane produced were 53.35% and 52.85%, respectively. Microbial assessment was performed by using Next Generation Sequencing (NGS) of 16S ribosomal RNA technique. Clostridium sp. was related to biohydrogen production methanotroph such as Cyclobacteriaceae, Saprospiraceae and Chloroflexi that were inhibited after the heat treatment. Heat treatment of inoculums is not suitable for the production of both biohydrogen and biomethane since it inhibits the methanogens. Thus, controlling operating conditions were important for hydrogen-producing bacteria as well as methanogens for biohydrogen and biomethane production.